INCREASING SOCIAL STATUS OF WOMEN IN THE YEARS OF INDEPENDENCE (IN THE CASE OF SURKHANDARYA REGION) - Rajbova Sabohat Bobirovna (Journal of Learning on History and Social Sciences, 2024)
In this article, in 1999-2004, opinions are given on the increase of the social status of women in the family and society and the legal protection of their labor. Resolution No. 117 of March 17, 1999, adopted by the Cabinet of Ministers "On preferential taxation of the income of women working in extremely harmful and difficult working conditions", in addition to protecting the interests of women and girls, adopted during the years of independence many decisions also focused on their importance in women's lives. The role of the "Year of Women" state program adopted in 1999 in the lives of women of Surkhandarya region was highlighted